Visiting Decision Model: Products, Prices, and Digital Marketing Through Consumer Satisfaction - Salim, Emil; Ali, Hapzi; Yulasmi, Yulasmi (Universitas Pendidikan Ganesha, 2023)
The tourism sector is very important in the country's foreign exchange earnings, a developed tourism sector should be supported by products, prices, and how tourism carries out its digital marketing. However, due to the lack of products, prices, and marketing offered, the tourism sector in Solok Regency experienced a decrease in tourist visits. The purpose of this study is to analyze factors that are considered relevant to influence visiting decisions, namely products, prices, and digital marketing. This type of research is causal research with data collection methods through surveys and questionnaire dissemination, and with a sample of 100 respondents. The data analysis technique used is Structural Equation Modeling (SEM) using SmartPLS 3.0 software, Hypothesis Test using SmartPLS 3.0. The results stated that product variables and digital marketing had a positive and significant effect on visiting decisions. However, the price stated that it did not affect the decision to visit. The implication of this study is that tourism managers must also prioritize developments that occur in the tourism industry so that tourist attractions are not left behind in the face of competition with other tourist attractions.